2009
DOI: 10.1111/j.1476-5381.2008.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular calcification and secondary hyperparathyroidism of severe chronic kidney disease and its relation to serum phosphate and calcium levels

Abstract: Background and purpose:Various complications consequent on disordered calcium and phosphate homeostasis occur frequently in chronic kidney disease (CKD) patients. Particularly, vascular calcification has high morbidity and mortality rates. There is a clear need for a better CKD model to examine various aspects of this disordered homeostasis. Experimental approach: Oral dosing with adenine induced CKD in rats in only 10 days. Serum calcium, phosphate and parathyroid hormone were measured and calcification in ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 33 publications
(84 reference statements)
5
50
0
1
Order By: Relevance
“…Only few experimental studies made a direct comparison between calcium and noncalcium phosphate binders on the development of uremia-related arterial calcifications. Recently, Terai et al 93 nicely showed that when serum phosphate and PTH were equally controlled by sevelamer and calcium carbonate, both agents significantly reduced the development of medial calcifications, although a slightly better outcome was seen with sevelamer which was probably attributable to lower serum calcium levels. These experimental data suggest that the traditional calcium containing phosphate binders are not necessarily harmful in CKD patients, particularly not in those without vascular calcification at the start of treatment, provided the calcium balance is regularly monitored and no adynamic bone disease is diagnosed.…”
Section: Experimental Evaluation Of Therapies For the Prevention Of Vmentioning
confidence: 99%
See 1 more Smart Citation
“…Only few experimental studies made a direct comparison between calcium and noncalcium phosphate binders on the development of uremia-related arterial calcifications. Recently, Terai et al 93 nicely showed that when serum phosphate and PTH were equally controlled by sevelamer and calcium carbonate, both agents significantly reduced the development of medial calcifications, although a slightly better outcome was seen with sevelamer which was probably attributable to lower serum calcium levels. These experimental data suggest that the traditional calcium containing phosphate binders are not necessarily harmful in CKD patients, particularly not in those without vascular calcification at the start of treatment, provided the calcium balance is regularly monitored and no adynamic bone disease is diagnosed.…”
Section: Experimental Evaluation Of Therapies For the Prevention Of Vmentioning
confidence: 99%
“…The consistent onset and progression of aortic medial calcification is most likely caused by the more severe hyperphosphatemia, 92 because in this synthetic diet, less protein-bound phosphate and more anorganic phosphate is present, with the latter being much more bioavailable. Another promising alternative was recently explored by Terai et al, 93 dosing rats orally through gavage with adenine for 10 days. Unfortunately, only about one third of the animals presented aortic calcification after 15 weeks.…”
Section: The Adenine-induced Chronic Renal Failure Ratmentioning
confidence: 99%
“…However, in a recent report of a modified version of the adenine model, weight loss was not an issue. Instead of using a chow-based adenine diet, Terai et al [39 ]orally dosed adenine at 600 mg/kg/day for 10 days as the initial acute insult to induce CKD in Wistar rats. On a normal diet with or without high phosphate (i.e.…”
Section: Adenine Rat Modelmentioning
confidence: 99%
“…Treatment with VDR activators, targeted at PTH levels, affects mineral metabolism, bone, and the arterial wall, but few clinical tools are currently available for monitoring the safety and efficacy of such a powerful therapy. Thus, although hypercalcemia is an indicator of vitamin D toxicity, it should be noted that in animals with CKD, vascular calcification can be induced not only by high [95], but also low doses of calcitriol [94,161] in the absence of hypercalcemia. Similarly, although the PTH level plays a central role in the therapeutic strategy, bone biopsy studies in children have shown that PTH levels are not a good indicator of bone morphology [43,162,163].…”
Section: Other Vdr Activatorsmentioning
confidence: 96%